(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Logistics continually meets new challenges, and is changing faster now than at any time in the past. Every business whether it is B2B or B2C all requires an efficient logistics service provider which delivers goods to the final customers timely. Now a days, there are many examples like zomato, swiggy, amazon in which the main element of success in the market and to win over competitor is an effective delivery/logistics mechanism. As the competition in logistics industry increasing day-by-day, almost all logistics companies are trying hard to satisfy their customers in terms of time promised for delivering the shipment to the final destination also called as TAT ( Turn Around Time ). Business always wonts to choose those logistics service provider who’s TAT is minimum as compared to others and at the same time efficiency in promising TAT is greater than others. Therefore, in logistics industry the key factor for analysing the effectiveness of a company in the industry is TAT and this TAT is also a main factor for measuring & analysing service standards of any logistics company. Thus this research paper which is based on primary data collected from real time data processing at Delhivery Private Limited, aims to measure and analyse service standards at different stages and also highlighting the main causes of discrepancies in breaching TAT in each individual stages.